The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/08957959.2013.828716
|View full text |Cite
|
Sign up to set email alerts
|

Reducing peanut allergens by high pressure combined with polyphenol oxidase

Abstract: Polyphenol oxidase (PPO) has been shown to reduce major peanut allergens. Since high pressure (HP) can increase enzyme activity, we postulated that further reduction of peanut allergens can be achieved through HP combined with PPO. Peanut extracts containing caffeic acid were treated with each of the following: (1) HP; (2) HP + PPO; (3) PPO; and (4) none. HP was conducted at 300 and 500 MPa, each for 3 and 10 min, 37 • C. After treatment, SDS-PAGE was performed and allergenic capacity (IgE binding) was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Liang found a positive effect on pineapple juice, with a reduction in allergenicity that correlated with increasing pressure and a maximum reduction of approximately 20% under 500 MPa (Liang et al, 2015). A greater reduction of the major peanut allergens and IgE-binding capacity was induced when using a high-pressure treatment at 500 MPa combined with polyphenol oxidase (Chung, Houska, & Reed, 2013). Acero-Lopez et al (2012) reported that OVT treated with high pressure and different pH levels resulted in changes in the sulfhydryl groups, surface hydrophobicity, enthalpy, and intrinsic fluorescence, along with partial aggregation.…”
Section: Introductionmentioning
confidence: 95%
“…Liang found a positive effect on pineapple juice, with a reduction in allergenicity that correlated with increasing pressure and a maximum reduction of approximately 20% under 500 MPa (Liang et al, 2015). A greater reduction of the major peanut allergens and IgE-binding capacity was induced when using a high-pressure treatment at 500 MPa combined with polyphenol oxidase (Chung, Houska, & Reed, 2013). Acero-Lopez et al (2012) reported that OVT treated with high pressure and different pH levels resulted in changes in the sulfhydryl groups, surface hydrophobicity, enthalpy, and intrinsic fluorescence, along with partial aggregation.…”
Section: Introductionmentioning
confidence: 95%